STRATEGIES FOR LIFELONG LEARNING AND EARNING FOR YOUTH – AN OVERVIEW - S. Baluchamy
life Long learning and earning empowers young people, by producing in them an appreciation of the independence and positive life choices. Hands on training is one of the most appropriate ways to organise effectively life long education programme in India. The NGO's have a vital role in spreading the movement. The present study is an overview of the various strategies, features and various perspectives of life long learning.